Old Futures - Lothian, Alexis (New York University Press, 2019)
'Old Futures' traverses the history of imagined futures from the 1890s to the 2010s, interweaving speculative visions of gender, race, and sexuality from literature, film, and digital media. Centering works by women, queers, and people of colour that are marginalized within most accounts of the genre, the text offers a new perspective on speculative fiction studies while reframing established theories of queer temporality by arguing that futures imagined in the past offer new ways to queer the present.
10.18574/9781479854585
Keywords: Criticism; interpretation; etc.; Afrofuturism.; American fiction.; British fiction.; LGBT.; affect.; black feminism.; black queer studies.; blackness.; digital.; dystopia.; empire.; eugenics.; fandom.; fantasy.; fascism.; feminism.; film.; futurity.; gay.; gender.; lesbian.; media.; modernity.; music.; narrative.; negativity.; new media.; pleasure.; politics.; punk.; race.; remix.; reproduction.; science fiction.; sexuality.; slash fiction.; slavery.; speculation.; technology.; television.; temporality.; transnational.; utopia.; vampire.; vidding.; video.; violence.; visual culture.; whiteness.; world-building.; world-making.; Speculative fiction.; Gender identity in literature.; Future; The; in literature.; LITERARY CRITICISM; Speculative fiction